HIV-1 Tat increases the adhesion of monocytes and T-cells to the endothelium in vitro and in vivo: implications for AIDS-associated vasculopathy. - Matzen, Kathrin; Dirkx, Anita E.M; Egbrink, Mirjam G.Aoude; Speth, Cornelia; Götte, Matthias; Ascherl, Gudrun; Grimm, Thomas; Griffioen, Arjan W; Stürzl, Michael (Virus Research, 2004)
HIV-1-infected patients exhibit severe damages of the aortic endothelium, develop angioproliferative lesions such as Kaposi's sarcoma (KS), and have an increased risk of cardiovascular diseases and atherosclerosis. An increased adhesion of leukocytes to the endothelium is a common pathogenic parameter of AIDS-associated vascular diseases. Here we show that the HIV-1 Tat protein, a regulatory protein of HIV-1 released by infected cells, and TNF-alpha, a cytokine increased in sera and tissues of HIV-1-infected patients, activate synergistically the adhesion of leukocytes to endothelial cells both in vitro and in vivo. This effect is selectively mediated by HIV-1 Tat, since HIV-1 Nef, another HIV-1 regulatory protein, and the HIV-1 envelope protein gp41, had no effect. In vitro adhesion assays with PBMC and quantitative cell type analysis of adherent cells by FACS demonstrated that HIV-1 Tat selectively activates the adhesion of T-cells and monocytes but not of B-cells. Intravital microscopic studies in mice confirmed the synergistic activity of HIV-1 Tat and TNF-alpha on leukocyte adhesion to the endothelium in vivo. These data indicate that HIV-1 Tat in cooperation with TNF-alpha may contribute to the vascular damage and cardiovascular diseases observed in AIDS patients but also to the prominent extravasation of T-cells and monocytes which is a key process in the formation and progression of KS lesions.